Basic presynaptic functions in hippocampal neurons are not affected by acute or chronic lithium treatment - Lüke, Katharina; Kaiser, Tobias; Svetlitchny, Alexei; Welzel, Oliver; Wenzel, Eva M.; Tyagarajan, Shiva; Kornhuber, Johannes; Groemer, Teja W. (Journal of Neural Transmission, 2014)
Lithium is an effective mood-stabilizer in the treatment of bipolar affective disorder. While glycogen synthase kinase 3-mediated and inositol depletion-dependent effects of lithium have been described extensively in literature, there is very little knowledge about the consequences of lithium treatment on vesicle recycling and neurotransmitter availability. In the present study we have examined acute and chronic effects of lithium on synaptic vesicle recycling using primary hippocampal neurons. We found that exocytosis of readily releasable pool vesicles as well as recycling pool vesicles was unaffected by acute and chronic treatment within the therapeutic range or at higher lithium concentrations. Consistent with this observation, we also noticed that the network activity and number of active synapses within the network were also not significantly altered after lithium treatment. Taken together, as lithium treatment does not affect synaptic vesicle release at even high concentrations, our data suggest that therapeutic effects of lithium in bipolar affective disorder are not directly related to presynaptic function.
EVALuna2:23623